REVIEW TEKNIK MIKROENKAPSULASI PADA EKSTRAK MANGOSTEEN - Rosa Riau Wati; Sriwidodo Sriwidodo; Anis Yohana Chaerunisa (JCPS (Journal of Current Pharmaceutical Sciences), 2020)
Mangosteen ( Garcinia mangostana L. ) is a popular tropical fruit that is widely found in southeast Asia . One of the important compounds in mangosteensal extract is Xanthones which underlies its various pharmacological activities . Mangosteen has characteristics, is unstable, reactivity , and is very easily oxidized, as well as poor solubility and bioavability. which can inhibit the formulation process. So that the microencapsulation method is used to protect the bioactive compounds in mangosteen extract, namely xanthones so that they can last a long time and can still be utilized properly by the body. Microencapsulation is the process by which a liquid is packaged or coated by a polymeric material . to produce micro sizes, called microcapsules . There are several methods of microencapsulation, frezee draying, spray draying, cooling, fluid bed coating, coacervation, and liposome entrapment . in the microencapsulation technique the material used in coating can be in the form of a polymer. Each polymer has different characteristics and purpose of use and variations of polymers that are tailored to the needs. The polymer to be used is capable of providing a cohesive thin layer with core material and chemically blended but still inert. Keyword: Mangosteen , Microencapsulation, Method, Polymer